PENINGKATAN KADAR EUGENOL PADA MINYAK CENGKEH DENGAN MENERAPKAN PROSES ADSORPSI - Herman Bangngalino; Ridhawati Tahir; Nurfiansyah; Firda; Muhaimin, (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
Research has been carried out to increase eugenol levels in clove oil by applying adsorption. The adsorption process was carried out using zeolite which had been activated using H2SO4 1M with a soaking period of 2 hours at a temperature of 90oC. The adsorption process was carried out at a temperature of 60oC using variable zeolite weight and adsorption time. The oil that has gone through the adsorption process was then analyzed. Based on the analysis results, the clove oil produced still did not pass the SNI 06-2387-2006 standard